Distributional effect of the farmer pension program in Taiwan: A regression-based decomposition analysis. Issue 1 (30th July 2018) - Luh, Yir-Hueih; Wei, Min-Fang
Abstract : Purpose: The Old Farmer Pension Program (OFPP) represents Taiwan's long-standing efforts aiming at improving farm household income and well-being; however, how effective the pension program is in terms of achieving the policy agenda has remained unclear. The paper aims to discuss this issue. Design/methodology/approach: Based on data drawn from the Survey of Family Income and Expenditure during 1999–2013, two identification strategies are used to examine the effect of OFPP. First the authors apply the Blinder-Oaxaca decomposition to address the concern if the program reaches the socially/economically disadvantaged farm households. The second identification strategy involves using the static and dynamic decomposition approaches to identify the major factors contributing to farm household income inequality and the redistribution role of the OFPP. Findings: Results from the Blinder-Oaxaca decomposition indicate that about 60 percent of the income gap can be eliminated if the pension recipients' socio-economic characteristics are the same as the non-recipient group, suggesting it is the disadvantaged group that receives the old farmer pension. Moreover, the results suggest the significant contributions of household investments in health and human capital as well as diversification toward nonfarm activities, to income inequality among Taiwan's farm households. Results from the dynamic decomposition suggest that the first-wave adjustment of the OFPP enlarges farm household income inequality, the following two waves of adjustment, however, plays an equalizing role. Originality/value: This study adds to the literature by providing a methodological refinement promoting the view that it calls for the use of the dynamic (change) decomposition framework to investigate the inequality-enlarging or inequality-equalizing role each income determinant plays.